Mapping Quantitative Trait Loci That Influence Serum Insulin-Like Growth Factor Binding Protein-5 Levels in F2 Mice (MRL/MpJ X SJL/J) - MOHAN, SUBBURAMAN (2003)
Recent studies using twins and inbred strains of mice reveal evidence for genetic mechanisms contributing to variation in circulating levels of IGF-I, IGF-II, and IGF binding protein (IGFBP)-3. To examine the hypothesis that serum IGFBP-5 levels have a strong heritable component, we intercrossed two inbred strains of mice, MRL/MpJ and SJL, which exhibit 79% difference in serum IGFBP-5 levels (554 ± 68 vs. 309 ± 51 ng/ml respectively, P < 0.001). A genome-wide scan was carried out using 137 polymorphic markers in 633 F2 female mice. Serum IGFBP-5 levels in the F2 progeny showed a normal distribution with an estimated heritability of 74%. Whole genome-wide scans for cosegregation of genetic marker data with high or low serum IGFBP-5 levels revealed six different quantitative trait loci (QTL) in chromosomes 1, 9 (two), 10, and 11 (two), which together explained 24% of F2 variance. Chromosome 11 QTL exhibited the highest LOD score (7.5). Based on the past findings that IGFBP-5 is an important bone formation stimulator, we predicted IGFBP-5 to contribute to bone mineral density variation in F2 mice. Accordingly, we found two of the six IGFBP-5 QTLs (Chrs 1 and 11) identified for serum IGFBP-5 phenotype also showed significant association with total body bone mineral density phenotype (measured by dual energy x-ray absorptiometry) in the F2 mice.